(untitled) (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article, the service of achieving the company’s main goal, such as the creation of appropriate departments for the implementation of the management function of marketing in companies, comprehensive study of environmental conditions, orientation to market requirements, and ensuring its flexibility in the foreign market, is considered.